Pilot-scale supercritical CO2 extraction coupled molecular distillation and hydrodistillation for the separation of essential oils from artemisia argyi Lévl. et Vant. Issue 18 (12th December 2021) - Zhong, Jia-Lun; Muhammad, Nadeem; Chen, Shun-Quan; Guo, Li-Wei; Li, Jia-Sheng
ABSTRACT: The essential oils of Artemisia argyi Lévl. et Vant were extracted and separated using three methods, hydrodistillation (HD), supercritical fluid extraction (SFE), and SFE coupled molecular distillation (SFE-MD). Various extraction parameters of SFE were optimized by process modeling of Hansen solubility parameters which are 30 MPa, temperature 45°C, no co-solvents, extraction time 2 h, and flow rate of 90 kg/h. The essential oils obtained by HD and SFE-MD have similar major compositions. The antimicrobial activities were examined according to the agar well diffusion method and the minimum inhibition concentrations against Staphylococcus aureus and Escherichia coli were compared.Abbreviations A. argyi, Artemisia argyi ; CFU, Colony Forming Unit; DMSO, dimethylsulfoxide; E. coli, Escherichia coli ; GC-MS, Gas Chromatography-Mass Spectrometer; HD, hydrodistillation; HSP, Hansen solubility parameters; MIC, minimum inhibition concentration; OSE, organic solvents extraction; RSM, response surface methodology; SCCO2, supercritical-CO2 ; SFE, supercritical fluid extraction; SFE-MD, SFE coupled molecular distillation; SMILES, Simplified Molecular Input Line Entry Syntax; S. aureus, Staphylococcus aureus ;